The Learning Power of Listening - Guijt, Irene; Gottret, Maria Veronica; Hanchar, Anna; Deprez, Steff; Muckenhirn, Rita (PRACTICAL ACTION PUBLISHING, 2022)
Steff had the pleasure to co-author the first SenseMaker Practitioner Guide with a group of friends and colleagues supported and published by Oxfam and CRS. This practical guide is for those who wish to use SenseMaker to conduct assessments, monitor progress, and undertake evaluations or research. Drawing on more than a decade of experience, the authors share dozens of examples from international development, providing practical tips and ideas for context-specific adaptations. They show how the method can be used to for difficult-to-measure outcomes related to poverty reduction, social justice, peacebuilding, resilience, gender norms, behavior change, governance and environmental management. ​ SenseMaker is a unique participatory method of inquiry that encourages and enables novel insights not obtained from conventional quantitative and quantitative and qualitative methods. It is action-oriented and, therefore, well-suited for people needing data- informed insights for adaptive management. "Writing this guide together with Irene, Veronica, Anna and Rita was an enormous learning process in itself and has further shaped our thinking and practice. We hope it will support first-time and experienced users to enhance their practice and that it will inspire people to explore and innovate further with the method."

Complexity Leadership Theory (CLT) - Abbaszada, Ramiz (2022)
The present literature review was conducted in order to investigate the role of Complexity Leadership Theory (CLT) in modern public administration. We use data from different academic articles to decompose the value within the framework of this theoretical perspective. In addition to explaining how extend, Complexity Leadership Theory (CLT) is crucial in the “information age” and its main factors will be the main priorities of the study. Traditional top-down conceptions of leadership are at best unduly simplistic, as twenty-first-century management continues to stress decentralized organizing structures and co-evolutionary ecologies of enterprises, institutions, and markets. There's also a growing recognition that effective leadership isn't always defined by the leader's symbolic, motivating, or charismatic behaviors. But, if leadership isn't "in" or "done by" a leader, how can we understand what leadership is and where it comes from? A unique method to answering these concerns is based on complexity theory, specifically the idea that leadership emerges from relational interactions among actors. Leadership, in this view, is more than a talent, a transaction, or a symbol; it comes from dynamic relationships. The role of leadership in accelerating those processes in companies where interdependent acts among many persons merge into a collective venture is investigated by "complexity leadership theory." Complexity leadership is a combination of the three forms of leadership described below: (1) administrative leadership based on tight control and a large bureaucratic hierarchy (2) adaptive leadership, which is built on creative issue solution, resonating with changing situations, and learning, and (3) action-centered leadership, which entails crisis decision-making and dynamic productivity.